Egg parasitoids of the processionary moth Thaumetopoea pityocampa (Den. & Schiff.) collected in Albania (Bollettino di zoologia agraria e bachicoltura, 2024)
Egg parasitoids and egg parasitism were studied in 32 egg batches of thepine processionary moth collected near Korca/ Albania in heights of 1050-1400 m inAugust-September 1997, after caterpillars' hatch. In this mountainous region, Baryscapusservadeii (Dom.) was most abundant at the higher level, followed byOoencyrtus pityocampae (Mercet) at the lower level. Trichogramma sp. was onlyfound at 1400 m a.s.l. Additionally, the hyper-parasitoid Baryscapus transversalisGraham was established parasitizing dominantly the eggs placed near the beginningand the end of the batches. The grade of parasitism of the various egg batches variedfrom zero to 61 %. The emergence dynamics of the parasitoids showed a peak of B.transversalis in November of the year, in which the host eggs were layed. B. servadeiiemerged mainly in J anuary of the following year. A high percentage of egg parasitoidsdied in the eggs, mainly from O. pityocampae and the polyembryonic Trichogrammasp. (see also Tsankov et al., 1996a); up to 12 pupae were found in one egg.
Keywords: Thaumetopoea pityocampa; egg parasitoids; Albania; hyper-parasitism; mortality of egg parasitoids; phenology